2005
DOI: 10.1016/j.amepre.2005.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Screen-Viewing Behaviors Among Preschoolers

Abstract: Background-Childhood obesity has emerged as a public health concern in Canada. It has been suggested that excessive screen viewing (i.e., television, computer, video) is a major factor contributing to the increased risk of obesity in children. Exploring young children's experiences with this modifiable behavior may be beneficial to the creation of a multifaceted program aimed at the primary prevention of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 22 publications
8
98
0
1
Order By: Relevance
“…16 Recent research found that in contrast to parents of school-age children, parents of preschoolers were not concerned about screen time; however, they were concerned about the content of what their preschoolers were watching. 34 Parents of preschoolers were unaware of the linkage between excessive television viewing and the risk of childhood obesity. They perceived television as a useful educational and babysitting tool, and they used it as a coping strategy when handling multiple children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Recent research found that in contrast to parents of school-age children, parents of preschoolers were not concerned about screen time; however, they were concerned about the content of what their preschoolers were watching. 34 Parents of preschoolers were unaware of the linkage between excessive television viewing and the risk of childhood obesity. They perceived television as a useful educational and babysitting tool, and they used it as a coping strategy when handling multiple children.…”
Section: Discussionmentioning
confidence: 99%
“…They perceived television as a useful educational and babysitting tool, and they used it as a coping strategy when handling multiple children. 34 One could envision that parents who allow or encourage screen-viewing in early childhood might inadvertently create habits that become ingrained. By the time parents realize the potential negative health consequences of excessive S-RSBs on their school-aged children, it might be difficult or too late to change these behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Canadian and British research also provides insights on parental attitudes and perceived barriers to physical activity in preschoolers (11) , attitudes to screenviewing behaviours in preschoolers (12) and attitudes to both eating and exercise in 7-12-year-olds (13) . Screen-viewing attitudes have also been investigated in American parents of 6-13-year-old children (14) .…”
mentioning
confidence: 99%
“…Studies have shown an association between TV viewing and body fat in toddlers and young children (Blair et al, 2007;Jackson, Djafarian, Stewart, & Speakman, 2009). Similarly, Dennison, Erb, and Jenkins (2002) found that higher levels of TV viewing in 1-5 year olds was significantly associated with their likelihood of being overweight, and research has consistently implicated extensive TV screen time with childhood obesity (Harrison, Burns, McGuinness, Heslin, & Murphy, 2006;He, Irwin, Sangster Bouck, Tucker, & Pollett, 2005;Subrahmanyam, Kraut, Greenfield, & Gross, 2000). While it would be expected that the link between time spent watching TV and weight issues was due to a displacement in time spent on physical activity, in fact, studies have shown the sedentary nature of watching TV has a unique relationship with health risks.…”
Section: Tv Screen Time and Physical Healthmentioning
confidence: 99%
“…However, there appears to be evidence of discord between expert guidelines, parental awareness of such guidelines, and their attitudes towards them. A study by Christakis (2009) found that only 6% of parents were aware of the American Academy of Paediatrics guidelines, while He et al (2005) found that parents of young children questioned the rationale of such guidelines limiting screen time. A national survey conducted by Northwestern University in 2013 found that just over half of parents (55%) were unconcerned about the media content their children were exposed to, and in fact generally believed that media on TV and mobile devices can have positive effects on children's academic skills (Parenting in the Age of Digital Technology: A National Survey, 2013).…”
Section: Parental Guidelines For Screen Timementioning
confidence: 99%